2018
DOI: 10.1017/s1751731117001306
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the economic impact of subclinical ketosis in dairy cattle using a dynamic stochastic simulation model

Abstract: The objective of this study was to estimate the economic impact of subclinical ketosis (SCK) in dairy cows. This metabolic disorder occurs in the period around calving and is associated with an increased risk of other diseases. Therefore, SCK affects farm productivity and profitability. Estimating the economic impact of SCK may make farmers more aware of this problem, and can improve their decision-making regarding interventions to reduce SCK. We developed a dynamic stochastic simulation model that enables est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 26 publications
1
72
0
3
Order By: Relevance
“…Quantifying the losses due to ketosis will enable veterinarians and farmers to make more informed decisions regarding the prevention and treatment of the disease. Some studies compared the economic consequences of various treatment strategies [7][8][9], whilst many more studies estimated the economic consequences of SCK and CK [9][10][11][12][13][14]. Raboisson et al [11] and Mostert et al [12] estimated average costs for a cow with SCK at €257 and €130 respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantifying the losses due to ketosis will enable veterinarians and farmers to make more informed decisions regarding the prevention and treatment of the disease. Some studies compared the economic consequences of various treatment strategies [7][8][9], whilst many more studies estimated the economic consequences of SCK and CK [9][10][11][12][13][14]. Raboisson et al [11] and Mostert et al [12] estimated average costs for a cow with SCK at €257 and €130 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These differences are probably due to the use of other model types and also different assumptions and input values. For instance, Raboisson et al [11] developed a static model, while Mostert et al [12] developed a dynamic model and thus simulated milk production, reproduction and culling over time. Also, the studies modeled the effect of SCK on culling differently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schuberth, 2 and Ch. Kühn 6,11 diseases also show metabolic disorders (Raboisson et al, 2014;Vercouteren et al, 2015;Mostert et al, 2018), and several authors have demonstrated the connection between the capacity of immunological defense strategies and metabolic regulatory mechanisms (Overton and Waldron, 2004;Roche et al, 2017;Wankhade et al, 2017). In the future, it will be important to reconcile economic efficiency and ethical requirements by breeding cows that are high-yielding as well as healthy and long-lived.…”
Section: Introductionmentioning
confidence: 99%
“…Increased costs of milk production result also from the incidence of metabolic diseases. Based on their investigations conducted in Holland Mostert et al (2018) reported that subclinical ketosis and the related health conditions generate average annual costs per 1 case amounting to EUR 130 (ranging from EUR 39 to EUR 348).…”
Section: Discussionmentioning
confidence: 99%